2018
DOI: 10.1051/epjam/2018002
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of photo-induced magnetic and chiral microscopy

Abstract: Light-matter interactions enable the perception of specimen properties such as its shape and dimensions by measuring the subtle differences carried by an illuminating beam after interacting with the sample. However, major obstacles arise when the relevant properties of the specimen are weakly coupled to the incident beam, for example when measuring optical magnetism and chirality. To address this challenge we propose the idea of detecting such weakly-coupled properties of matter through the photo-induced force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Theoretically, if a chiral sample and the nanoprobe were illuminated with chiral light the photoinduced force would be different depending on the chirality of the light. 95 This principle has been shown to have credibility through the modelling of a chiral sphere in the presence of chiral light.…”
Section: Photoinduced Magnetic Force Microscopy (Pimfm)mentioning
confidence: 98%
“…Theoretically, if a chiral sample and the nanoprobe were illuminated with chiral light the photoinduced force would be different depending on the chirality of the light. 95 This principle has been shown to have credibility through the modelling of a chiral sphere in the presence of chiral light.…”
Section: Photoinduced Magnetic Force Microscopy (Pimfm)mentioning
confidence: 98%
“…The APB and RPB are obtained by superposing Laguerre Gaussian beams with opposite angular momenta [29], [31], [32], [37], [68]. The electric field vector in an APB propagating along the +z-direction (optical axis of the beam) is polarized along the azimuthal direction  in the transverse plane that, after suppressing the time dependence exp( ) , where 0 w and  are, respectively, the beam parameter and the excitation wavelength.…”
Section: A Optimally-chiral Arpb Illuminationmentioning
confidence: 99%
“…. Furthermore, neglecting the field's phase difference between the tip-apex and sample, due to their subwavelength distance, it is shown that the difference between the forces exerted on the tip-apex for two CP plane wave illuminations with opposite handedness reads 27,47,48  …”
Section:  mentioning
confidence: 99%
“…In this regard, the z -component of the general force expression of eq reduces to (see eq 2.2 of ref and eq of ref ) . Furthermore, neglecting the field’s phase difference between the tip-apex and sample, due to their subwavelength distance, it is shown that the difference between the forces exerted on the tip-apex for two CP plane wave illuminations with opposite handedness reads ,, in which ε 0 is the vacuum permittivity and d is the center-to-center distance between the sample and tip-apex. Note that in deriving this formula we assume CP plane waves with electric field magnitude | E 0 | on the beam axis since it simplifies our analytical calculations.…”
Section: Probing the Transverse Handedness Of Chiral Samplesmentioning
confidence: 99%